Digital Transformation, ESG, and Sustainable Performance of Rural Sharia Agritourism Microenterprises - Fabellany Sovina; Hamdi Agustin; Annisa Mardatillah; Sufian Hamim (Mandalika Institute, 2026)
Rural Sharia agritourism microenterprises play an important role in promoting local economic development, community empowerment, and sustainable rural transformation. However, these enterprises continue to face significant challenges related to digitalization, sustainability practices, limited human resource capacity, and changing market dynamics. This study aims to develop a comprehensive conceptual understanding of how digital transformation, Environmental, Social, and Governance (ESG), human resource readiness, Islamic business values, and local wisdom collectively contribute to the sustainable performance of rural Sharia agritourism microenterprises. This study employed a qualitative literature review using a library research approach by synthesizing recent scholarly publications published between 2017 and 2026. The literature was analyzed through qualitative content analysis and thematic synthesis to identify recurring patterns, conceptual relationships, and research gaps. The findings indicate that sustainable business performance cannot be explained by digital transformation or ESG implementation independently. Instead, sustainable performance emerges from the complementary interaction among digital capability, sustainability-oriented management, human resource readiness, ethical business practices, and community-based cultural values. Human resource readiness serves as an enabling capability that strengthens the implementation of digital transformation and ESG, while Islamic business values and local wisdom reinforce ethical governance, stakeholder trust, and social legitimacy. This study contributes to the literature by integrating Resource-Based View, Dynamic Capability Theory, Stakeholder Theory, and Human Capital Theory into a unified conceptual framework for sustainable rural entrepreneurship. The proposed framework also provides practical insights for policymakers, rural development agencies, and microenterprise owners seeking to strengthen the resilience and long-term competitiveness of rural Sharia agritourism microenterprises.